2016
DOI: 10.18632/oncotarget.11336
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ARC decreases the survival of HEI-OC-1 cells after neomycin damagein vitro

Abstract: Hearing loss is a common sensory disorder mainly caused by the loss of hair cells (HCs). Noise, aging, and ototoxic drugs can all induce apoptosis in HCs. Apoptosis repressor with caspase recruitment domain(ARC) is a key factor in apoptosis that inhibits both intrinsic and extrinsic apoptosis pathways; however, there have been no reports on the role of ARC in HC loss in the inner ear. In this study, we used House Ear Institute Organ of Corti 1 (HEI-OC-1) cells, which is a cochlear hair-cell-like cell line, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…HEI-OC1 cells, a HC-like cell line, express several molecular markers of cochlear HCs, including calbindin, calmodulin, math1, myosin7a, and prestin28293031, and they are commonly used to study the protection of HCs. We used Myosin 7a as the HC marker, and immunostaining showed that all HEI-OC1 cells could be double labeled by Myosin 7a and c-Myb, demonstrating that c-Myb is expressed in HEI-OC1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HEI-OC1 cells, a HC-like cell line, express several molecular markers of cochlear HCs, including calbindin, calmodulin, math1, myosin7a, and prestin28293031, and they are commonly used to study the protection of HCs. We used Myosin 7a as the HC marker, and immunostaining showed that all HEI-OC1 cells could be double labeled by Myosin 7a and c-Myb, demonstrating that c-Myb is expressed in HEI-OC1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ototoxic drugs cause hearing loss by inducing HC apoptosis, primarily by altering the MMP of the mitochondria ( Huang et al, 2000 ; Wu et al, 2002 ; Sun et al, 2015 ; Guan et al, 2016 ; He et al, 2016 ; Yu et al, 2017 ). Mitochondria play an important role in cell metabolism, and aminoglycoside-induced apoptosis is closely related to mitochondrial dysfunction, which leads to decreased MMP and increased ROS ( Joza et al, 2001 ; Chipuk et al, 2004 ; Coffin et al, 2013 ; Sun et al, 2014 , 2015 ; Mei et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that HC loss induced by ototoxic drugs is commonly associated with ROS accumulation, which induces mitochondrial depolarization and initiates apoptosis ( Marcotti et al, 2005 ; Mcfarland et al, 2007 ; Shan et al, 2014 ; Guan et al, 2016 ; He et al, 2016 ; Liu et al, 2016 ; Yu et al, 2017 ). We evaluated the levels of mitochondrial ROS in HEI-OC1 cells after cisplatin and H 2 O 2 treatment and found that the ROS level was significantly decreased after MA2 treatment compared to the cisplatin and H 2 O 2 treatment group ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%